Making Dents in the Paradigm of a Perfect Wife: Parvati’s Negotiations with Patriarchy in Indian Mythology - Sahgal, Smita; Malik, Vinita (Advances in Social Sciences Research Journal, 2023)
Pārvatī is a fascinating figure in Indian mythology and generally what stands out is her absolute love for Śiva who, too, could not ignore her. Popular folklore reiterates the notion of their timeless love and rituals concretize it. Purāṇas do mention her as a goddess of mountains in her own right, but her character gets principally demarcated by her closeness to her husband, Śiva, for whom she could die to avenge humiliation meted out to him by her father in her Satī form. Subsequently, she was reborn as Pārvatī to seek that proximity again. Historically if she was a mother goddess in her own right, we are curious to know how her cult got amalgamated within that of Śiva. Purāṇas give us clues about this process of assimilation and in the course raise a litany of issues that we would attempt to answer in our paper.